Differential Diffusional Properties in Loose and Tight Docking Prior to Membrane Fusion - Witkowska, Agata; Spindler, Susann; Mahmoodabadi, Reza Gholami; Sandoghdar, Vahid; Jahn, Reinhard (Biophysical Journal, 2020)
Fusion of biological membranes, although mediated by divergent proteins, is believed to follow a common pathway. It proceeds through distinct steps, including docking, merger of proximal leaflets (stalk formation), and formation of a fusion pore. However, the structure of these intermediates is difficult to study because of their short lifetime. Previously, we observed a loosely and tightly docked state preceding leaflet merger using arresting point mutations in SNARE proteins, but the nature of these states remained elusive. Here, we used interferometric scattering (iSCAT) microscopy to monitor diffusion of single vesicles across the surface of giant unilamellar vesicles (GUVs). We observed that the diffusion coefficients of arrested vesicles decreased during progression through the intermediate states. Modeling allowed for predicting the number of tethering SNARE complexes upon loose docking and the size of the interacting membrane patches upon tight docking. These results shed new light on the nature of membrane-membrane interactions immediately before fusion.
CRIS-Team Scopus Importer:2020-12-11